Analyzing the Influence of Anxiety and Aggression on the Performance of Volleyball Players - Karisiddaiah Wodiyar E (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
Anxiety and aggression are critical psychological factors influencing athletic performance, particularly in high-intensity, fast-paced sports like volleyball, where players must demonstrate quick decision-making, precision, and resilience under pressure; this study aims to analyze the relationship between competitive state anxiety, sports aggression, and performance outcomes among university-level volleyball players by utilizing validated psychological inventories to assess cognitive anxiety, somatic anxiety, and self-confidence, as well as instrumental and hostile aggression in a sample of male and female athletes aged 17–21, with findings indicating that moderate levels of anxiety positively correlate with enhanced focus, reaction time, and strategic play, while excessive anxiety impairs concentration, increases muscle tension, and disrupts coordination, ultimately hindering performance, whereas instrumental aggression, characterized by controlled assertiveness, serves as a performance enhancer by increasing competitive drive and tactical assertiveness, but hostile aggression, driven by emotional impulsivity, leads to poor decision- making, penalties, and reduced team cohesion, highlighting the need for structured psychological conditioning programs incorporating stress management techniques, cognitive-behavioral strategies, and controlled aggression training to optimize mental resilience and competitive efficiency, with implications for coaches, sports psychologists, and athletes in developing personalized intervention strategies that maximize performance potential while mitigating the negative impacts of anxiety and aggression in competitive volleyball.